Venous microtrauma associated with pharmacomechanical catheter-directed thrombolysis in a large animal acute deep venous thrombosis model - Mohamed S. Zaghloul; Sophia R. Pyeatte; Sophia R. Pyeatte; Shahab Hafezi; Usama Ismail; Rodrigo Meade; Batool Arif; Roger Rowe; Luis Sanchez; Mohamed A. Zayed; Mohamed A. Zayed; Mohamed A. Zayed; et al. (Frontiers in Cardiovascular Medicine)
BackgroundPharmacomechanical catheter-directed thrombolysis (PCDT) is commonly used to treat acute deep venous thrombosis (DVT). The AngioJet Rheolytic Thrombectomy (ART) device is a widely used option. However, previous serious adverse events led to an FDA black-box warning. Limited large animal studies have assessed ART's efficacy and safety. We investigated the periprocedural outcomes and venous histomorphic impact of ART in a novel large animal acute DVT model.MethodsSix adult male Yorkshire pigs (96–113 kilograms) underwent general anesthesia and continuous hemodynamic monitoring. Acute DVT was induced in the infrarenal IVC using occlusive balloons. Three pigs were treated with ART's thrombectomy mode (MT) for 10 min. Another three pigs underwent PCDT with 250 ml saline and 50,000 IU Streptokinase over 10 min. Serial venograms assessed thrombus formation and post-treatment results, and then iliocaval venous segments were resected for histomorphic analysis.ResultsART significantly reduced thrombus in all pigs without complications (64.7% ± 9.7% vs. 16.1% ± 10.5%; P = 0.02). Retroperitoneal staining was observed around treated venous segments in all pigs, with a higher mean staining score in the PCDT group compared to the MT group (2 ± 0 vs. 1.3 ± 0.57; P = 0.11). Histopathology revealed more venous wall intimal tears in ART-treated segments compared to untreated segments (18 ± 5.79 vs. 6.3 ± 2.51, P = 0.01).ConclusionsART effectively removes acute thrombus in a large animal DVT model without periprocedural complications. The observed retroperitoneal staining following PCDT raises some concerns regarding venous wall integrity following ART, for which the long-term consequences are unknown.